2017
DOI: 10.1039/c7dt03364h
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic properties of a cobalt metal–organic framework with a zwitterionic ligand synthesized in situ

Abstract: Herein we describe the high yield synthesis of a highly crystalline cobalt(ii) MOF with a novel zwitterionic ligand made up of 3,3',4,4'-BPTC and 1,4-cyclohexanediamine, obtained in situ during the hydrothermal synthesis. The compound with the molecular formula CHNOCo·2HO has a molecular mass of 965.7783 g mol, a triclinic crystalline system (a = 5.86 Å, b = 9.28 Å, c = 19.92 Å, α = 83.93°, β = 88.01°, γ = 78.59), it is thermally stable up to 300 °C and presents structural stability before and after removing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Thus, in connection with our interests in the application of MOFs in catalysis 19 and in the development of sustainable chemical protocols, 20 herein we describe the straightforward methods for the click (CuAAC) and Biginelli multicomponent reactions, employing Cu(INA) 2 -MOF and the [Cu(INA) 2 (H 2 O) 4 ] complex as catalysts, under solvent-free conditions. We found that the click reaction was fast and selective for the synthesis of 1,4-disubstituted-1,2,3-triazoles, including the synthesis of triazoles containing a selenium atom.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in connection with our interests in the application of MOFs in catalysis 19 and in the development of sustainable chemical protocols, 20 herein we describe the straightforward methods for the click (CuAAC) and Biginelli multicomponent reactions, employing Cu(INA) 2 -MOF and the [Cu(INA) 2 (H 2 O) 4 ] complex as catalysts, under solvent-free conditions. We found that the click reaction was fast and selective for the synthesis of 1,4-disubstituted-1,2,3-triazoles, including the synthesis of triazoles containing a selenium atom.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Yaghi and coworks reported a 2-D titanium−organic framework with imine ligands in situ condensated. 33 Such strategies have demonstrated cyclisation, 34 dehydrogenative or oxidative coupling, 35,36 hydroxylation, 35,37 hydrolysis, [38][39][40] cleavage of the S−S bonds, 41,42 imine condensation, 33,43 cycloaddition of organic nitriles 44,45 and C-C heterocoupling; in the latter case amorphous hybrid porous materials were produced. 46 More recently, diazo coupling, imidizatio and condensation of boronic acids 47 were also reported to be candidates for one pot strategy during the preparation of this manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Yaghi and coworks reported a 2-D titanium−organic framework with imine ligands in situ condensated. 33 Such strategies have demonstrated cyclisation, 34 dehydrogenative or oxidative coupling, 35,36 hydroxylation, 35,37 hydrolysis, [38][39][40] cleavage of the S−S bonds, 41,42 imine condensation, 33,43 cycloaddition of organic nitriles 44,45 and C-C heterocoupling; in the latter case amorphous hybrid porous materials were produced. 46 More recently, diazo coupling, imidizatio and condensation of boronic acids 47 were also reported to be candidates for one pot strategy during the preparation of this manuscript.…”
Section: Introductionmentioning
confidence: 99%